(untitled) (Research, Society and Development, 2022)
Emerging in the city of Wuhan, China in December 2019, the SARS-CoV-2 virus was an outbreak of infection that quickly spread to several countries due to its high transmission rate. In Brazil, the first cases were registered in February 2020. The study aimed to analyze the epidemiological evolution of SARS-CoV-2 and present the conceptions of people who contracted the virus, identifying how they went through that moment. The survey was conducted through a virtual strategy, Google Forms®, the period for obtaining the answers was from June 23 to 29, 2020. This study covered the North, Northeast, Southeast and Midwest regions. In October 2020, Brazil has already surpassed more than 4,969,141 million infected people, considering that, of the 75 people, 73 said they had already contracted COVID-19 and the others had not been contaminated with the virus. The most prevalent symptoms were headache, sore throat, discomfort and diarrhea, the most frequent being fever, runny nose, cough, shortness of breath, tiredness, pain and loss of taste or smell. The measures adopted by respondents are in accordance with those disclosed by the Ministry of Health, Brazilian Society of Pulmonology and Phthisiology (SBPT). When asked if they suffer prejudice daily after the disease is cured, most answered yes, that is, after the cure of COVID-19, most people report having suffered prejudice, mainly in public environments, the lack of information from society it makes individuals feel excluded, afraid or even embarrassed to approach others. Based on this assumption, social isolation measures are disseminated by health agencies as the main way to protect themselves against the virus, however, many people had to break this isolation for mandatory activities, such as working.